Challenging the imperial mode of living by challenging ELSEWHERE: spatial narratives and justice - Dünckmann, Florian; Hein, Jonas; Klepp, Silja (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
This article frames imperial lifestyles as a problem of global justice and discusses the spatial logic that engenders the actual discrepancy between this moral standard of equal rights and reality. It claims that the notion of ELSEWHERE, as Brand and Wissen (2022) put it, plays a central role in understanding the conditions that allow this grossly unjust global separation between responsibility and effect to be stable. In doing this, it establishes the concept of communities of justice that determine the boundaries of moral responsibility and analyses the global spatial logic that underlies the course of these boundaries, as they are experienced in everyday life. The Westphalian system of sovereign nation states is its main component but certainly not the only one. Finally, it sheds light on current attempts to challenge this spatial logic as well as their potentials and limitations.